2017
DOI: 10.1021/jacs.7b08349
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Structures Arise Naturally During Ligand Exchange in Metal–Organic Frameworks

Abstract: Examination of the microstructure of metal-organic frameworks (MOFs) after postsynthetic exchange (PSE) reveals that the exchanged ligand is concentrated at the edges of the crystal and decreases in concentration with crystal depth, resulting in a core-shell arrangement. Diffusion studies of the carboxylate ligand into MOF-5 indicate that diffusion is limiting to the exchange process and may ultimately be responsible for the observed core-shell structure. Examination of PSE in UMCM-8 and single crystals of UiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
136
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(142 citation statements)
references
References 21 publications
5
136
0
1
Order By: Relevance
“…PSE has since been demonstrated to be as imple,y et powerful, tool to introduce functionalities in the crystal structure of highly stable Zr-MOFs that are not accessible via direct synthesis. [4] Recent reports have shed some light onto microstructural aspects,e videncing that either homogeneous solid solutions [5] or core-shell architectures [6] can be formed upon PSE, mainly depending on crystal size.The possible role of defects during PSE has not yet been the object of thorough investigation, even though it is now well established that Zr-MOFs can contain alarge number of defects. [7] Defects reduce the connectivity of the [Zr 6 O 4 (OH) 4 ] 12+ clusters by substitution of bridging dicarboxylate linkers with terminal groups, usually monocarboxylates derived from crystallisation modulators used during the synthesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PSE has since been demonstrated to be as imple,y et powerful, tool to introduce functionalities in the crystal structure of highly stable Zr-MOFs that are not accessible via direct synthesis. [4] Recent reports have shed some light onto microstructural aspects,e videncing that either homogeneous solid solutions [5] or core-shell architectures [6] can be formed upon PSE, mainly depending on crystal size.The possible role of defects during PSE has not yet been the object of thorough investigation, even though it is now well established that Zr-MOFs can contain alarge number of defects. [7] Defects reduce the connectivity of the [Zr 6 O 4 (OH) 4 ] 12+ clusters by substitution of bridging dicarboxylate linkers with terminal groups, usually monocarboxylates derived from crystallisation modulators used during the synthesis.…”
mentioning
confidence: 99%
“…[4] Recent reports have shed some light onto microstructural aspects,e videncing that either homogeneous solid solutions [5] or core-shell architectures [6] can be formed upon PSE, mainly depending on crystal size.The possible role of defects during PSE has not yet been the object of thorough investigation, even though it is now well established that Zr-MOFs can contain alarge number of defects. [7] Defects reduce the connectivity of the [Zr 6 O 4 (OH) 4 ] 12+ clusters by substitution of bridging dicarboxylate linkers with terminal groups, usually monocarboxylates derived from crystallisation modulators used during the synthesis. [8] Recent reports have evidenced that monocarboxylates grafted at defective sites can be readily exchanged with other monocarboxylates [8c, 9] or even with phosphonates, [10] phosphinates, [11] and sulfate.…”
mentioning
confidence: 99%
“…Through postsynthetic modification of linkers, portions of the linkers in the crystal can be further transformed to form MOFs with hierarchical compositions . Core–shell structures can be obtained from postsynthetic exchange with linker exchange in MOF‐5, UMCM‐8 (where UMCM = University of Michigan Crystalline Material), and UiO‐66 . Additionally, MOFs can change their shapes to obtain hierarchical compositions by ligand exchange.…”
Section: Mofs With Hierarchical Compositionsmentioning
confidence: 99%
“…Further development of solvent‐assisted ligand‐exchange strategies should focus on the precise control of reaction active sites and the extent, which allow the rational design of desirable functionalities in the target MOF or COF materials. In order to precisely explore the ligand‐exchange strategies, MOF‐5 was selected as a model system to examine the ligand exchange process with benzene‐2,3,5,6‐d 4 ‐1,4‐dicarboxylic acid (H 2 BDC‐d 4 ) as probed ligand . Raman spectra showed that the exchanged ligand is concentrated at the edges of the crystal and decreases in concentration with crystal depth, resulting in a core–shell arrangement, because of the slow diffusion of the carboxylic acid ligand into the pores of the MOF.…”
Section: Rational Design Of the Diverse Catalytic Sites In Crystallinmentioning
confidence: 99%